Diesel exhaust exposure, its multi-system effects, and the effect of new technology diesel exhaust. (May 2018) - Reis, Haley; Reis, Cesar; Sharip, Akbar; Reis, Wenes; Zhao, Yong; Sinclair, Ryan; Beeson, Lawrence
Abstract: Exposure to diesel exhaust (DE) from vehicles and industry is hazardous and affects proper function of organ systems. DE can interfere with normal physiology after acute and chronic exposure to particulate matter (PM). Exposure leads to potential systemic disease processes in the central nervous, visual, hematopoietic, respiratory, cardiovascular, and renal systems. In this review, we give an overview of the epidemiological evidence supporting the harmful effects of diesel exhaust, and the numerous animal studies conducted to investigate the specific pathophysiological mechanisms behind DE exposure. Additionally, this review includes a summary of studies that used biomarkers as an indication of biological plausibility, and also studies evaluating new technology diesel exhaust (NTDE) and its systemic effects. Lastly, this review includes new approaches to improving DE emissions, and emphasizes the importance of ongoing study in this field of environmental health. Highlights: Diesel exhaust exposure induces inflammation, oxidative stress, and tissue damage. Inflammatory markers are used to demonstrate the presence of changes in different organ systems due to DE exposure. DE exposure is linked to both carcinogenic and non-carcinogenic multi-system effects. New Technology Diesel Exhaust and Alternative fuels decrease harmful effects traditionally induced by DE.